Smoking and Islamic Law: A Study of K.H. Lanre Said al-Bugisi's Perspective - Syandri, Syandri; Kasim, M.; Yudiman, Muhammad Ariel (Cakrawala: Jurnal Studi Islam, 2024)
This study aims to analyze the ruling of smoking from the perspective of K.H. Lanre Said al-Bugisi's fiqh. Employing a qualitative research method with a literature review approach, this study reveals that K.H. Lanre Said al-Bugisi developed a unique methodology of ijtihad, combining a deep understanding of the Qur'an and Sunnah with the use of reason (istimbāṭ al-‘aqlī). In the context of smoking, he did not find explicit evidence in the sacred texts. Therefore, he applied general Islamic principles to determine its ruling. The research findings indicate that K.H. Lanre Said al-Bugisi categorized the ruling of smoking into three based on its health impacts: haram if it is harmful, makruh if it worsens an existing disease, and mubah if it does not cause negative effects. This study contributes significantly to understanding the dynamics of ijtihad in addressing contemporary issues such as smoking.